Antimicrobial analysis of honey against Staphylococcus aureus isolates from wound, ADMET properties of its bioactive compounds and in-silico evaluation against dihydropteroate synthase - Uwem Okon Edet; Elizabeth Nkagafel Mbim; Esu Ezeani; Okoroiwu Uchechi Henshaw; Oju R. Ibor; Ini Ubi Bassey; Edet Effiong Asanga; Ekpo Eyo Antai; Francisca O. Nwaokorie; Bassey Okon Edet; Glory P. Bebia; Curtis Tega; et al. (BMC, 2023)
Abstract Background One of the main challenges of wound healing is infection with multi-drug resistant (MDR) bacteria such as Staphylococcus aureus. The spectrum of antibiotics used to treat them is declining; thus, there is a need for alternatives. Our study was designed to evaluate the antimicrobial properties of honey, its pharmacokinetics (ADMET) properties and in-silico analysis of its bioactive compounds against dihydropteroate synthase of S. aureus using trimethoprim as control. Methods Standard protocols were employed in collection and preparation of samples, generation of canonical strings, and conduction of microbiological analyses. Bioactive compounds' ADMET properties were evaluated using the SWISSADME and the MCULE toxicity checker tools. The MCULE one-click docking tool was used in carrying out the dockings. Results The gas chromatography-mass spectrophotometry revealed twenty (20) bioactive compounds and was dominated by sugars (> 60%). We isolated a total of 47 S. aureus isolates from the wound samples. At lower concentrations, resistance to trimethoprim (95.74 to 100.00%) was higher than honey (70.21 to 96.36%). Only seven (7) isolates meet Lipinski's rule of five and ADMET properties. The docking scores of the bioactive compounds ranged from -3.3 to -4.6 while that of trimethoprim was -6.1, indicating better binding or interaction with the dihydropteroate synthase. The bioactive compounds were not substrates to P450 cytochrome enzymes (CYP1A2, CYP2CI9 and CYP2D6) and p-glycoprotein, indicating better gastrointestinal tract (GIT) absorption. Conclusion The favourable docking properties shown by the bioactive compounds suggest they could be lead compounds for newer antimetabolites for management of MDR S. aureus.